2019
DOI: 10.1111/bld.12295
|View full text |Cite
|
Sign up to set email alerts
|

Special Olympics: Athletes' perspectives, choices and motives

Abstract: Accessible summary There is a need for more voiced opinions from Special Olympic (SO) athletes in contemporary literature. Five SO athletes presented their own views on their experiences of participating in sport. SO athletes would welcome more autonomy, responsibility and roles in their everyday sporting participation. Implications for coaches and parents are presented as a consequence of sporting involvement. Abstract BackgroundIn the past, academic literature and research relating to the Special Olympic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
3
0
3
Order By: Relevance
“…4446,58 Other studies found that coaches implemented practices that encouraged life skills development. 57–59 However, some athletes interviewed in Dluzwwaska-Martyniez's 56 study stated that some Special Olympics coaches, although not intentionally, adopt behaviors that block their thletes' autonomy and decision-making; thus, limiting their life skills and personal development opportunities. Coaches in other studies reported observing positive changes in their athletes pertaining to different life skills (e.g., social skills, team work) and psychological outcomes (e.g., self-confidence).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4446,58 Other studies found that coaches implemented practices that encouraged life skills development. 57–59 However, some athletes interviewed in Dluzwwaska-Martyniez's 56 study stated that some Special Olympics coaches, although not intentionally, adopt behaviors that block their thletes' autonomy and decision-making; thus, limiting their life skills and personal development opportunities. Coaches in other studies reported observing positive changes in their athletes pertaining to different life skills (e.g., social skills, team work) and psychological outcomes (e.g., self-confidence).…”
Section: Discussionmentioning
confidence: 99%
“…44,45 It is important to note that the majority of the studies only used self-reported measures to assess coaches’ behaviors and intentions of teaching their athletes life skills. 4446,57,58 Only one study measured coaches’ use of instructional behaviors with observational measures (i.e., Sherlock-Shangraw 59 ). Within this study, coaches had extensive coaching experience which could have positively influenced coaches’ practices regarding life skills teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Na autodeterminação (continnum motivacional) os atletas com DI presentes no estudo, apresentam valores de motivação autónoma mais elevada comparativamente aos restantes. O desporto constitui-se como uma atividade positiva para atletas com DI (Haigh et al, 2013), dado que para este tipo de desportista é necessário desenvolver condutas autodeterminadas, com o intuito de se efetuar um transfer destas competências para o quotidiano, com vista à melhoria de qualidade de vida (Everett et al,2019;Hernández et al2021., Martins et al,2022. Na investigação realizada por Moltó e Bruna (2017), os desportistas com DI também demonstram maior relevância na motivação autónoma.…”
Section: Conclusãounclassified
“…Assim o desporto tem um efeito transformador na vida dos atletas dos Special Olympics (Everett et al, 2019). Deste modo torna-se necessário, aumentar a produção científica que examine a relação entre a teoria da autodeterminação, necessidades psicológicas básicas e bem-estar subjetivo (Frielink et al, 2018), cuja associação é um bom indicador de qualidade de vida dos atletas com deficiência intelectual (Frielink et al, 2018).…”
Section: Conclusãounclassified
See 1 more Smart Citation